Global perspectives on youth gang behavior, violence, and weapon use - Harding, Simon; Palasinski, Marek (Advances in psychology, mental health, and behavioral studies, 2016)
"This book reconsiders the traditional understandings of youth violence in various forms, such as gang activities, criminal behavior, and weapons use, focusing on the psychosocial elements of violence among children, teenagers, and young adults"--Provided by publisher.